Alterations of gut microbiome following gastrointestinal surgical procedures and their potential complications - Tsigalou, Christina; Paraschaki, Afroditi; Bragazzi, Nicola Luigi; Aftzoglou, K.; Stavropoulou, Elisavet; Tsakris, Z.; Vradelis, S.; Bezirtzoglou, Eugenia (Frontiers in Cellular and Infection Microbiology, 2023)
Intestinal microorganisms play a crucial role in shaping the host immunity and maintaining homeostasis. Nevertheless, alterations in gut bacterial composition may occur and these alterations have been linked with the pathogenesis of several diseases. In surgical practice, studies revealed that the microbiome of patients undergoing surgery changes and several post-operative complications seem to be associated with the gut microbiota composition. In this review, we aim to provide an overview of gut microbiota (GM) in surgical disease. We refer to several studies which describe alterations of GM in patients undergoing different types of surgery, we focus on the impacts of peri-operative interventions on GM and the role of GM in development of post-operative complications, such as anastomotic leak. The review aims to enhance comprehension regarding the correlation between GM and surgical procedures based in the current knowledge. However, preoperative and postoperative synthesis of GM needs to be further examined in future studies, so that GM-targeted measures could be assessed and the different surgery complications could be reduced.